DETERMINAN STATUS GIZI ANAK BALITA DARI KELUARGA NELAYAN DI WILAYAH PUSKESMAS TILOTE KABUPATEN GORONTALO TAHUN 2010 - Tumenggung, Imran (Sainstek, 2011)
The lack of nutrient in children below five years old can cause disorder in growth and development. This has become a national health problem. The aim of the study was to find out determinants which correlate with nutritional status of children below five years old of the fisherman family at the Tilote Public Health Center in Gorontalo regency. The study was a cross sectional study which was conducted from August to October 2010. The number of samples was 200 children below five years old selected by simple random sampling. The data were analyzed by using bivariate and multivariate analysis. The results of bivariate analysis indicate that nutritional status (height/age) of children below five years old correlates with mothers education (p = 0.004), knowledge (p = 0.000), upbringing pattern (p = 0.000), energy consumption (p = 0.003), protein consumption (p = 0.032), and infectious disease (p = 0.016). Bivariate analysis indicate that nutritional status (weight/height) correlates with mothers education (p = 0.004), knowledge (p = 0.000), upbringing pattern (p = 0.009), energy consumption (p = 0.000), and infectious disease (p = 0.000). The multivariate analysis indicates that knowledge of mother is the most dominant factor correlating with the nutritional status of children below five years old based on height/age (p = 0.000; Wald = 47.556), and so is infectious disease based on weight/height (p = 0.001; Wald = 12.037).Efforts to improve maternal nutrition knowledge as well as efforts to prevent and control infectious diseases in children under five years old from the fisherman family are necessary.